2012
DOI: 10.1001/jama.2012.36522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2- vs 4-Week Attending Physician Inpatient Rotations on Unplanned Patient Revisits, Evaluations by Trainees, and Attending Physician Burnout

Abstract: RAINEES LEARN INPATIENT MEDI-cine on the job, providing clinical care to patients as members of ward teams led by attending physicians. Although the structures of these ward teams vary by local educational heritage and hospital policy, 1,2 a prevailing trait is that attending physicians are assigned to them for only 2 continuous weeks-a duration that is half of the previous standard. 3,4 Both trainees 3 and educational leaders 5 have decried short rotations as disruptive because they truncate studentteacher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 42 publications
0
35
0
2
Order By: Relevance
“…[17] Two-week rotations have been shown to reduce burnout compared with four-week rotations for general medicine attendings. [18]…”
mentioning
confidence: 99%
“…[17] Two-week rotations have been shown to reduce burnout compared with four-week rotations for general medicine attendings. [18]…”
mentioning
confidence: 99%
“…5 One study found that medical students perceived worse teaching with a 2-week compared with a 4-week attending block. 6 In contrast, another study reported that medical students found similar teaching effectiveness between shorter and longer faculty rotations. 7 Previous studies have also found that learners think shorter faculty rotations reduce attending physicians' ability to evaluate them.…”
Section: Discussionmentioning
confidence: 96%
“…7 Previous studies have also found that learners think shorter faculty rotations reduce attending physicians' ability to evaluate them. 4,6 However, published research is limited by data derived from surveys and evaluation scores that do not well describe the reasons students prefer working with faculty for shorter or longer periods of time. Previous studies have not used qualitative research methods, an important strategy for exploring student perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, more studies could be undertaken to determine whether rotations for residents and attending physicians should be lengthened or better synchronized. 5 Methods of reducing stress that leads to burnout could be developed that might enable rotations to be lengthened, including reducing the need for onerous, duplicative, and usually useless documentation by both attendings and residents. 6 Programs could aim for more continuity with shorter shifts by making sure that returning residents care for the same panels of patients they had signed over earlier.…”
Section: F or Physicians Who Were Residents In The 1970smentioning
confidence: 99%